Frameworks for health systems performance assessment: how comprehensive is Ghana's holistic assessment tool? - Emmanuel Kumah; Samuel E. Ankomah; Adam Fusheini; Emmanuel Kusi Sarpong; Eric Anyimadu; Ato Quist; Brian Koomson (BMC, 2020)
Abstract Background Measuring the performance of a health system is an essential requirement in creating systems that generate efficient, equitable, patient-focused, accessible and sustainable results. A fundamental requirement for a performance measurement system is the development of an assessment framework within which specific performance measures could be defined and applied regularly. This paper examines the comprehensiveness of Ghana's health system assessment framework called the Holistic Assessment Tool in relation to some of the internationally recognized frameworks. The paper also analyzes trends in the performance of the health system to understand whether or not an improvement has been recorded following the adoption and implementation of the Holistic Assessment Tool. Methods Mainly secondary data were used in this analysis. Searches were conducted on Google Scholar, PubMed, Scopus and Science Direct between May and July, 2019 for published documents on health system performance assessment. We also obtained unpublished documents from Ghana's Ministry of Health, Ghana Health Service website, and Ghana Statistical Service database. Descriptive statistics were used to examine trends in the performance of the Ghanaian health system. Results While the tool provides a national framework for evaluating the performance of the Ghana Health system in several domains, the Holistic Assessment Tool does not cover key health system domains such as information systems for health, access to essential medicines, and patient-centeredness. Also, the scope of the assessment program seems limited to the evaluation of the Ministry of Health's annual plans, programs and projects. However, the health system has recorded improvements in population health indicators, such as life expectancy at birth, infant mortality, under-5 mortality, HIV prevalence and disease burden (in terms of disability adjusted life years). Conclusions The Holistic Assessment Tool is a useful framework, but needs further refinement, both in scope and in conceptual robustness. Future studies should consider exploring factors influencing performance of the Ghanaian health system. Such information will help in strategizing for better and more improvements.